Pendampingan Proses Pendaftaran Sertifikasi Halal Di Desa Gejlig Kecamatan Kajen Kabupaten Pekalongan - Alifia Salsabila; Nagita Shinta Ramadanti; Reni Dian Safitri (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2023)
The globalization of the halal lifestyle has prompted Indonesian consumers to choose Shariah-compliant products, halal food, Muslim clothing, Muslim-friendly entertainment, and halal trade. Indonesia has significant potential as a market and producer of halal products, involving 1.6 million small-scale food enterprises. Starting in October 2024, halal certification will be mandatory for all food products in Indonesia. However, many small businesses are still reluctant to apply for certification due to a lack of awareness. This research was conducted in Gejlig Village, Kajen District, Pekalongan, involving 30 small businesses. The aim was to educate them on the importance of halal certification and registration procedures. The results showed that the training effectively improved their understanding, motivated them to apply for certification, and enhanced product quality and market reach.